Academic Discrimination Against Persons with Disabilities in Higher Education - Anindya, Felicia; Yudyantoro, Jutta Aurora Citra; Maharani, Arindy; Setiawan, Aris (Universitas Negeri Surabaya, 2025)
Higher education is expected to function as an inclusive and equitable space for all individuals, including persons with disabilities; however, academic discrimination persists in structural and cultural forms. Although Law Number 8 of 2016 guarantees the right to education, its realization raises critical theoretical concerns regarding the effectiveness of legal protection. This study aims to conceptualize academic discrimination in higher education and to examine the adequacy of existing legal frameworks from a theoretical perspective. Using normative legal research with statute and conceptual approaches, this study analyzes legal norms and relevant literature. The findings reveal a fundamental gap between formal legal guarantees and their realization, indicating structural limitations within the legal system. The theoretical novelty of this research lies in the development of a normative–conceptual framework that positions academic discrimination as a manifestation of structural inequality rather than merely a failure of implementation. By integrating human rights theory, the social model of disability, and legal effectiveness theory, this study highlights the need to move from a formalistic legal paradigm toward substantive equality in ensuring the rights of persons with disabilities.